510 Case Series: Four cases of Orbital Extension of Cutaneous Squamous Cell Carcinoma and Their Management. (4th May 2021) - Gaston-Grubb, M; Boylan, C
Abstract: Introduction: Cutaneous squamous cell carcinoma (cSCC) invading the orbit is exceedingly rare. Understanding its presentation and management is of great value to the plastic surgeon. Method: Retrospective case series of four patients aged 54 to 88 years. All patients presented with cSCC of the face or scalp which infiltrated the orbit. All underwent tumour excision and appropriate reconstruction. Results: Case 1 and 2 involved cSCC originating from the right temporal and medial maxilla region, respectively. Case 1 posed the further challenge of irreversible blindness in the other eye, making exenteration very undesirable. In Case 2 the tumour extended along the infraorbital nerve and required several reconstructions of the eyelid to improve functionality and aesthetics. Cases 3 and 4 involved cSCC originating from the forehead and temporal region, respectively. Both required burring of the bony outer table and soft tissue reconstruction. Case 4 presented with the additional challenge of perineural spread to the cavernous sinus. Conclusions: This case series provides an insight into a rare, advanced presentation of cSCC. Eyeball exenteration has significant physical, aesthetic, and psychological impacts and therefore should be avoided if possible, particularly if the tumour has not breached the orbital septum.